Historical Disease Prevalence, Cultural Values, and Global Innovation. (January 2021) - Bennett, Daniel L.; Nikolaev, Boris
The historical prevalence of infectious diseases has had an enduring effect on innovation around the world. Building on the Parasite Stress Theory of Values, we propose a framework suggestive that the impact of historical disease pathogens on contemporary innovation is transmitted through the development of cultural values as an evolutionary psychological immune system response to ecological conditions. Economic and social interaction between groups was greater (limited) in countries with low (high) pathogen levels, resulting in the development of individualistic (collectivistic) values, which in turn encouraged (impeded) innovation. We provide supportive empirical evidence for a sample of 83 countries.